The nuclear organization of Polycomb/Trithorax group response elements in larval tissues of Drosophila melanogaster. - Fedorova, E.; Sadoni, N.; Dahlsveen, I.K.; Koch, J.; Kremmer, E.; Eick, D.; Paro, R.; Zink, D. (Chromosome Research, 2008)
We analysed the nuclear organization of the Polycomb/Trithorax group response element (PRE/TRE) Fab-7 and of other PRE/TREs in larval tissues of D. melanogaster. The results show that pairing/clustering of transgenic and endogenous Fab-7 elements and of other endogenous PRE/TREs occurs only to a limited degree in a highly locus-specific and tissue-specific manner. However, transgenic Fab-7 elements as well as the Fab-7-regulated Abd-B gene and other endogenous loci preferentially occupied defined nuclear regions. Preferred association with the nuclear periphery was observed in the inactive state. However, also in the active state, Fab-7 was often found associated with the nuclear periphery as well as with the boundary of heterochromatin in a fly line- and tissue-specific manner. The boundary between heterochromatin and euchromatin revealed a highly complex architecture in the three-dimensional nuclear space with a close juxtaposition of active and repressed domains. The results suggest that such complex architectures create nuclear microenvironments sustaining specific states of activity of defined PRE/TREs. However, the data also show that the positional behaviour of the transgenic Fab-7 element does not apply to PRE/TREs in general. Altogether, this finding and the highly locus-, tissue-, and fly line-specific behaviour with regard to nuclear positioning and pairing/clustering suggest that the relationships between nuclear organization and functional regulation of PRE/TREs are highly complex and that simple models making general predictions might not be appropriate.